Pengaruh Arus Kas Bebas, Leverage, dan Pertumbuhan Penjualan terhadap Kinerja Keuangan: (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Indah Chairunnisa; Indah Rahayu Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study was conducted to determine the Influence of Free Cash Flow Structure, Leverage, and Sales Growth on Financial Performance. This research was conducted on companies that go public in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) with a research period of 2019 – 2023. The sampling technique in this study uses the purposive sampling method and a sample of 53 companies going public in the property and real estate sector has met the sample criteria. The analysis technique used is multiple linear regression analysis using SPSS software version 22.0. The results of this study show that Free Cash Flow has a positive and significant effect on Financial Performance, Leverage has no significant effect on Financial Performance and sales growth has a significant positive effect on Financial Performance.